Après le Règne de Jésus. Aperçus de l'imaginaire des autochtones pentecôtistes de l'Ouest du Guatemala - Beaucage, Pierre; Ducos, Gerardo (Anthropologica, 2022)
The meaning of the mass conversions to Pentecostalism among indigenous peoples in Latin America has been and is still debated in anthropology. This paper, based on interviews completed in 2002 among the Quiche of Western Guatemala, reveals the presence of two tendencies, one, charismatic—millenarian and the other, institutional, in the discourse and imaginaries of members of local Pentecostal Churches, men and women, and their pastors. I conclude that both tendencies are present and in tension with each other, and diversely affect the people interviewed, according to gender and position in the hierarchy. The millenarian tendency insists on miracles and the role of the Spirit and seems to be strengthened by the permanent crisis of the impoverished countryside; the tendency towards institutionalization insists on morality and a deeper knowledge of the Word of God. It is based on the professional training of pastors and the resources which are controlled by national and international Churches. The former is apolitical, while the latter seeks accommodation with certain political forces.